Downton Abbey. Season 3 [videorecording (Blu-Ray)] - Fellowes, Julian (PBS Distribution, 2013)
The War is over and a long-awaited engagement is on, but all is not tranquil at Downton Abbey as wrenching social changes, romantic intrigues, and personal crises grip the majestic English country estate for a third thrilling season. In the wake of World War I, Robert, Earl of Grantham, sticks to his duty to maintain Downton more firmly than ever.